Cognitive Science and Artificial Intelligence Advances and Applications - Gurumoorthy, Sasikumar (Singapore : Springer Singapore, 2018)
This book presents interdisciplinary research on cognition, mind and behavior from an information processing perspective. It includes chapters on Artificial Intelligence, Decision Support Systems, Machine Learning, Data Mining and Support Vector Machines, chiefly with regard to the data obtained and analyzed in Medical Informatics, Bioinformatics and related disciplines. The book reflects the state-of-the-art in Artificial Intelligence and Cognitive Science, and covers theory, algorithms, numerical simulation, error and uncertainty analysis, as well novel applications of new processing techniques in Biomedical Informatics, Computer Science and its applied areas. As such, it offers a valuable resource for students and researchers from the fields of Computer Science and Engineering in Medicine and Biology.
1.Construction of Breast Cancer Based Protein Protein Interaction Network Using Multiple Sources of Datasets -- 2.A Novel Evolutionary Automatic Clustering Technique by Unifying Initial Seed Selection Algorithms and K-Means into Teaching-Learning-Based Optimization -- 3.Classification of Abnormal Blood Vessels in Diabetic Retinopathy using Neural Network -- 4.Flue-cured tobacco Leaves classification: A Generalized approach using Deep Convolutional Neural Networks -- 5.The Adaptive Strategies Improving Web Personalization Using the Tree Seed Algorithm (TSA) -- 6.An Experimental Evaluation of Integrated Dematal and Fuzzy Cognitive Maps for Cotton Yield Prediction.
Engineering
text file PDF
Keywords: Computational intelligence; Health informatics; Bioinformatics; Neural networks (Computer science) .; Biomedical engineering